Estimates for $λ$-spirallike function of complex order on the boundary - Akyel, T. (Ukrains’kyi Matematychnyi Zhurnal, 2022)
UDC 517.5We give some results for $λ$ -spirallike function of complex order at the boundary of the unit disc $U$. The sharpness of these results is also proved. Furthermore, three examples for our results are considered.